Analysis of the extracellular battlefield of potato blight disease - Ossorio Carballo, L (2022)
Antagonistic interactions between plant and pathogens trigger plant immune responses that rely on complex signalling networks in which molecules and proteins of diverse nature interact to avoid pathogen colonisation. On their side, plant pathogens have developed mechanisms to suppress plant immunity. Secreted hydrolases play a key role in early plant immunity as they can release pathogen molecules in the apoplast that can be sensed by plant receptors and pathogens secrete inhibitors to supress their activity. This suppression of hydrolase activities can help the pathogen to overcome plant defences and establish a compatible interaction causing disease. In this thesis we investigated apoplastic hydrolytic activities during infection by the causal agent of potato blight disease: the oomycete Phytophthora infestans. In chapter 2, we monitored the impact of leaf detachment in infection assays in the model organism Nicotiana benthamiana. We addressed the hydrolytic activity changes on the apoplast upon detachment and we used proteomics to examine protein changes in apoplast and total extract. We then assessed the impact of detachment in specific immune responses triggered by pathogen-associated molecular patterns and effectors. In chapter 3, we used ABPP coupled with mass spectrometry to study the active proteome of the tomato apoplast during early infection of P. infestans. We compared abundance and activity data to identify putative post translational regulation of apoplastic hydrolases activity. Additionally, we performed convolution ABPP coupled with mass spectrometry to discover novel suppressed tomato hydrolases upon P. infestans infection. Finally in chapter 4, we characterised a novel secreted cysteine protease from P. infestans using transient expression in planta. We confirmed the activity of the novel P. infestans protease and its inhibition by protease secreted inhibitors from P. infestans using ABPP and substrate-specific activity assays. Furthermore, we compared the expression patterns of the P. infestans protease and inhibitors throughout the time course of infection. Altogether, the present thesis provides an overview of how plant immunity is affected in detached leaves infection assays. It also provides evidence for novel apoplastic hydrolytic activity in the context the potato blight disease and dwells into the impact of apoplastic proteases in immunity.